The observational, cross-sectional study of drug utilization 90% and use of dipeptidyl peptidase-4 inhibitor in the patients with type 2 diabetes mellitus - Shivgunde, Prashant P.; Joshi, Shantanu R.; Kodilkar, Archana D. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Diabetes is a chronic metabolic disease which affects the quality of life. It leads to multiple complications due to metabolic involvement. Out of multiple drugs used to treat diabetes, dipeptidyl peptidase 4 (DPP-4) inhibitors are comparatively new drugs used for type-2-diabetes mellitus (DM) treatment. This study aimed to find out the drug utilization (DU) 90% and use of DPP-4 inhibitors in patients with type-2-DM. Methods: A prospective, cross-sectional, observational study was conducted at a private healthcare clinic of an endocrinologist in Nashik. Type-2-DM patients of both sexes were selected and a total of 199 patients were enrolled in the study. The consented patients were interviewed and prescription copies were collected. After studying them; statistical analysis was done and results and conclusions were drawn. Results: Out of total prescribed drugs, 58.77% of drugs were anti-diabetics. It was observed that the biguanides were most frequently (25.32%) prescribed while the least prescribed drugs were meglitinide analogues (0.08%). Most commonly utilized anti-diabetic found to be metformin. Vildagliptin 50 mg is the most commonly prescribed drug from DPP-4 inhibitors. Most of the drugs from the DPP-4 inhibitor group came under DU90%. Conclusions:DPP-4 inhibitors are showing wide acceptability by endocrinologists for type-2-DM management, according to this study. Performing repetitive drug utilization pattern study and circulation of standard treatment guidelines to practising physicians can be required. To emphasize the point on generic prescription, more awareness should be created. So that these can responses to further cost-effective and rational prescribing practices.